An exceed 60% efficiency Nd:YAG transparent ceramic laser with low attenuation loss effect - Chang, Jin-Quan; Shen, Yu; Bian, Qi; Zong, Nan; Lv, Ze; Bo, Yong; Peng, Qin-Jun (Frontiers in Physics, 2022)
Here, attenuation loss effect and laser performance enhancement of Nd:YAG transparent ceramics were investigated. Using a 0.6 at.% Nd:YAG ceramic rod with 3 mm diameter and 65 mm length, the scattering coefficient and absorption coefficient at 1064 nm were measured to be 0.0001 cm-1 and 0.0017 cm-1, respectively. For the 808 nm side-pumped laser experiment, an average output power of 44.9 W was achieved with an optical-to-optical conversion efficiency of 26.4%, which was nearly same with that of 1 at.% single crystal. Adopting the 885 nm direct end-pumped scheme, the following laser tests demonstrated the high optical efficiency of 62.5% and maximum output power of 144.8 W were obtained at absorbed pump power of 231.5 W. This was up to now the highest optical conversion efficiency acquired in Nd:YAG ceramic laser to our knowledge. It proves that high power and high efficiency laser output could be generated by high optical quality Nd:YAG ceramic rod along with the 885 nm direct pumping technology.